2014
DOI: 10.1093/europace/eut387
|View full text |Cite
|
Sign up to set email alerts
|

The OPTI-MIND study: a prospective, observational study of pacemaker patients according to pacing modality and primary indications

Abstract: The present analysis showed that frequent deviations occurred when comparing the device settings at discharge from the pacemaker implant in clinical practice to the available guidelines on pacing mode selection. Analysis of 2-year outcomes in the OPTI-MIND study will provide an insight into whether specific physiological settings could improve the quality of pacing with a positive effect on patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…6 Indeed, only 46.6% of patients with SSS and 28% of AVB patients in sinus rhythm received a strictly physiologic programming according to the generic principles of maintenance of AV synchrony, avoidance of unnecessary atrial/ventricular pacing when not indicated, allowance of rate increase in chronotropically incompetent patients. 7 Physiologic programming was not associated with increased mortality or hospitalizations. However, in the subgroup with AVB as primary rhythm disease, physiologic pacing was associated with a lower incidence of new-onset atrial tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…6 Indeed, only 46.6% of patients with SSS and 28% of AVB patients in sinus rhythm received a strictly physiologic programming according to the generic principles of maintenance of AV synchrony, avoidance of unnecessary atrial/ventricular pacing when not indicated, allowance of rate increase in chronotropically incompetent patients. 7 Physiologic programming was not associated with increased mortality or hospitalizations. However, in the subgroup with AVB as primary rhythm disease, physiologic pacing was associated with a lower incidence of new-onset atrial tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 95%
“…These criteria were used as a surrogate definition of physiologic pacing and used together with clinical variables to stratify clinical events of primary endpoint. According to the pre-specified secondary study endpoints 7 we investigated 1) the difference in the composite of cardiac cause mortality or first cardiac-related hospitalization between groups programmed with physiologic versus non-physiologic settings at baseline; 2) incidence at 2 years of documented atrial fibrillation (AF) episodes associated with any unplanned hospital visit, including hospitalizations for symptoms and/or treatment of AF in the subgroup of patients without AF as the primary rhythm disease at enrolment; 3) comparison between pacing settings at discharge and final programmed pacing parameters at 2 years; 4) clinical development of indications and/or upgrade to implantable cardioverter-defibrillator (ICD) or cardiac resynchronization device (CRT). Details on study design, together with analysis of baseline data have been previously published.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations